Characterization of the first cultured representative of a Bacteroidetes clade specialized on the scavenging of cyanobacteria - Wajdi Ben Hania; Manon Joseph; Boyke Bunk; Cathrin Spröer; Hans‐Peter Klenk; Marie‐Laure Fardeau; Stefan Spring (Environmental Microbiology, 2017)
Summary The anaerobic, mesophilic and moderately halophilic strain L21‐Spi‐D4 T was recently isolated from the suboxic zone of a hypersaline cyanobacterial mat using protein‐rich extracts of Arthrospira (formerly Spirulina ) platensis as substrate. Phylogenetic analyses based on 16S rRNA genes indicated an affiliation of the novel strain with the Bacteroidetes clade MgMjR‐022, which is widely distributed and abundant in hypersaline microbial mats and heretofore comprised only sequences of uncultured bacteria. Analyses of the complete genome sequence of strain L21‐Spi‐D4 T revealed a possible specialization on the degradation of cyanobacterial biomass. Besides genes for enzymes degrading specific cyanobacterial proteins a conspicuous transport complex for the polypeptide cyanophycin could be identified that is homologous to typical polysaccharide utilization loci of Bacteroidetes . A distinct and reproducible co‐occurrence pattern of environmental 16S rRNA gene sequences of the MgMjR‐022 clade and cyanobacteria in the suboxic zone of hypersaline mats points to a specific dependence of members of this clade on decaying cyanobacteria. Based on a comparative analysis of phenotypic, genomic and ecological characteristics we propose to establish the novel taxa Salinivirga cyanobacteriivorans gen. nov., sp. nov., represented by the type strain L21‐Spi‐D4 T , and Salinivirgaceae fam. nov., comprising sequences of the MgMjR‐022 clade.